Politik Anggaran: Hubungan Keuangan Antara Pemerintah Pusat dan Pemerintah Daerah - Rizka Amelia Armin; Nurul Adliyah; Ummu Habibah Gaffar (Institut Agama Islam Negeri Palopo, 2023)
This study discusses the financial relationship between the central government and regional governments. It examines the pattern of monetary authority in the implementation of regional autonomy to know the system of implementing regional autonomy and reviewing financial regulations related to the performance of regional autonomy. The results of this study show that regional autonomy can be fully implemented if the central government explicitly decentralizes financial authority and state financial laws are adjusted to the concept of autonomy. The relationship between central and regional financial controls in the context of autonomy still requires regulation. The results of this study become a reference to realize sustainable central and regional economic relations